Influence of dispersing agents on the rheology and early heat of hydration of blended cements with high loading of calcined marl. (July 2015) - Ng, S.; Justnes, H.
Abstract: The dispersing effectiveness of five commercial plasticizers; lignosulfonate (LS), naphthalene sulphonate–formaldehyde polycondensate (NSF) and three polycarboxylate ethers (PCEs) were quantitatively investigated in blended cements where ordinary Portland cement (OPC) was partly replaced by calcined marl (CM) up to 60%. CM drastically viscosified and decreased the flow of the cement due to high absorption of water. The performance of plasticizers mimics that in the OPC system except when PCEs were added. PCEs possessing long side chains were less effective as dispersants due to the consumption of these polymers via the ability of their PEO side chains to intercalate between the remaining layers in the calcined clay. Higher dosages were thus needed for effective dispersion. The decrease in PCE–OPC interaction led to little retardation in cement hydration except at high polymer dosages, whereas the performance of NSF and LS in CM blended cement is driven by clinker content.